The First Steps of Blended Mobility in European Higher Education: A Survey of Blended Intensive Programmes - O'Dowd, Robert; Werner, Sina (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Blended Mobility refers to the strategic combination of phases of online learning with periods of short physical mobility. This approach to international learning has gained considerable interest in European university education in recent years due to the introduction of Blended Intensive Programmes (BIPs) in the new Erasmus + programme. BIPs are defined as a form of Blended Mobility which involve short, intensive programmes that use innovative ways of learning and teaching, including online cooperation. This article reports on the results of a survey of BIP academic coordinators which was carried out to establish an overview of current practices in the area. The study provides an overview of the perceived benefits of Blended Mobility and also identifies the main challenges which practitioners encounter when running such programmes. A series of good practices which are recommended by organisers are presented and this is followed by a discussion of the survey's major conclusions.
Keywords: Blended Mobility; Blended Intensive Programm; Virtual Mobility; Virtual Exchange